Uptake, Accumulation and Toxicity of Silver Nanoparticle in Autotrophic Plants, and Heterotrophic Microbes: A Concentric Review - Tripathi, Durgesh K.; Tripathi, Ashutosh; Shweta,; Singh, Swati; Singh, Yashwant; Vishwakarma, Kanchan; Yadav, Gaurav; Sharma, Shivesh; Singh, Vivek K.; Mishra, Rohit K.; Upadhyay, R. G.; Dubey, Nawal K.; et al. (Frontiers in Microbiology, 2017)
Nanotechnology is a cutting-edge field of science with the potential to revolutionize today’s technological advances including industrial applications. It is being utilized for the welfare of mankind; but at the same time, the unprecedented use and uncontrolled release of nanomaterials into the environment poses enormous threat to living organisms. Silver nanoparticles (AgNPs) are used in several industries and its continuous release may hamper many physiological and biochemical processes in the living organisms including autotrophs and heterotrophs. The present review gives a concentric know-how of the effects of AgNPs on the lower and higher autotrophic plants as well as on heterotrophic microbes so as to have better understanding of the differences in effects among these two groups. It also focuses on the mechanism of uptake, translocation, accumulation in the plants and microbes, and resulting toxicity as well as tolerance mechanisms by which these microorganisms are able to survive and reduce the effect of AgNPs. The review differentiates the impact of silver nanoparticles at various levels between autotrophs and heterotrophs and signifies the prevailing tolerance mechanisms. With this background, a comprehensive idea can be made with respect to the influence of AgNPs on lower and higher autotrophic plants together with microbes and new insights can be generated for the researchers to understand the toxicity and tolerance of AgNPs in plants and microbes.